Catalytic Hydroboration of Organic Nitriles Promoted by Aluminum Complex. Issue 4 (20th December 2018) - Harinath, Adimulam; Bhattacharjee, Jayeeta; Panda, Tarun K.
Abstract: We demonstrate an efficient protocol for the chemoselective hydroboration of organic nitriles with pinacolborane (HBpin) and catecholborane (HBcat) using aluminum alkyl complex [ κ 2 ‐2‐F−C6 H4 NP(Se)Ph2 2 Al−(Me)] as a pre‐catalyst to afford diboryl amines under solvent‐free and mild conditions (60 °C) in high yield. The aluminum complex was prepared by the reaction of [2‐F−C6 H4 NHP(Se)Ph2 ] and trimethylaluminum in toluene. The solid‐state structure of Al complex is established. Nitriles with a wide array of electron‐withdrawing and electron‐donating functional groups were easily converted to the desired products through the formation of aluminum hydride as an active species. A kinetic study of the catalytic reaction is also reported. Abstract :